Effect of Quality Guidance and Counseling Facilities on Student Perceptions and Service - Aini, Jannatun; Hartini, Hartini; Harahap, Emmi Kholilah; Sofyan, Afriyadi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Guidance and counseling (GC) services play a pivotal role in supporting students’ academic, personal, and social development. However, their effectiveness is often constrained by inadequate facilities and infrastructure, which may influence students’ perceptions and the perceived quality of services. This study explicitly hypothesized that the completeness of GC facilities and infrastructure is positively associated with (1) students’ perceptions of GC services and (2) the overall service quality. A quantitative correlational design was adopted, involving 302 students (178 females, 124 males) aged 15–18 years across science and social science tracks from grades X–XII at MAN 1 Lubuklinggau City. Data were collected through a 70-item questionnaire, validated through product–moment correlation (r > 0.3338) and found to be highly reliable (Cronbach’s α = 0.972). Analytical methods were selected based on the data scale and research objectives: Spearman correlation tested the strength and direction of ordinal associations, simple linear regression examined predictive effects, and multivariate analysis of variance (MANOVA) assessed the simultaneous influence of infrastructure completeness on both dependent variables. The results showed that the completeness of GC facilities significantly and positively predicted both student perceptions (ρ = 0.681, p < 0.001) and service quality (β = 0.787, p < 0.001). MANOVA confirmed a strong combined effect (Wilks’ Λ = 0.157, p < 0.001; partial η² = 0.604), with 95% confidence intervals supporting the robustness of the findings. These results indicate that adequate physical and technological facilities substantially enhance students’ experiences and perceptions of GC services. Practically, schools are encouraged to construct private counseling rooms that meet national standards, integrate e-counseling platforms (e.g., BK-Smart, Zoom), and allocate BOS/DAK funds for upgrading GC infrastructure and digital tools. The findings underscore that investment in comprehensive and technology-supported counseling infrastructure is crucial for achieving professional and student-centered GC services.